Survival and prognostic factors for relapsed childhood acute lymphoblastic leukemia after treatment with the Chinese children’s cancer group ALL-2015 protocol: a single center results - Chen, Xia; Yu, Jie (Frontiers in Oncology, 2024)
IntroductionThis retrospective study was conducted to assess the survival rates and prognostic factors in children with relapsed acute lymphoblastic leukemia (ALL) who were treated according to the Chinese Children’s Cancer Group ALL-2015 protocol at the Children’s Hospital of Chongqing Medical University.MethodsThe study cohort involving 852 evaluable children with ALL reported a total of 146 relapses during a median follow-up period of 53 months. The primary outcomes measured were the second complete remission (CR2) rates, and 5-year event-free survival (EFS) and overall survival (OS) for patients who received re-treatment post-relapse. Patient data were stratified by ALL subtype (B-ALL vs. T-ALL), age at relapse, site of relapse, and timing of relapse. Univariate and multivariate analyses were performed to identify factors significantly associated with EFS and OS.ResultsAs of March 31, 2023, 146 relapses were observed, including 128 B-ALL and 18 T-ALL cases. The 8-year CIR was (19.8 ± 1.6)%, with no significant difference between B-ALL and T-ALL (P=0.271). Among the 105 patients who underwent re-treatment, 70 achieved CR2, resulting in a CR2 rate of 67.6%. The 5-year EFS and OS rates for re-treated patients were (45.0 ± 5.4)% and (56.9 ± 5.2)%, respectively. Significant differences in 5-year OS and EFS were found between B-ALL and T-ALL relapses (P < 0.001). The 5-year EFS and OS varied significantly with relapse timing and site of relapse. Factors significantly affecting EFS after relapse included the site of relapse, immunophenotyping, CR2 achievement, and hematopoietic stem cell transplantation (HSCT). Immunophenotyping, CR2 achievement, and HSCT were also identified as significant factors affecting OS after relapse.DiscussionDespite treatment with the CCCG-ALL-2015 protocol, a significant relapse rate was observed, with 72% of children opting for re-treatment post-relapse. The study highlights the importance of considering specific prognostic factors to inform tailored treatment strategies for relapsed childhood ALL. The findings emphasize the need for further research into improving therapeutic approaches for this patient population. This retrospective study was conducted to assess the survival rates and prognostic factors in children with relapsed acute lymphoblastic leukemia (ALL) who were treated according to the Chinese Children’s Cancer Group ALL-2015 protocol at the Children’s Hospital of Chongqing Medical University.